A model of academic dishonesty intentions: mediating effects of machiavellianism and differential association - Prince, Melvin; Wang, Emma (Journal of Further and Higher Education, 2024)
Past studies of academic dishonesty typically have been grounded in the theory of planned behaviour. Key predictors of academic dishonesty variables under this framework generally have been attitudes towards academic dishonesty, the impact of peer pressure to engage in such acts, and individual perceptions of related acts. However, planned behaviour theory is silent about the significant impact on academic dishonesty of past academic dishonesty behaviours. The objective of the present study is to analyse, through the lens of social learning theory, the effects of past behaviours that predispose academic dishonesty: differential association, i.e., the effects of individual learning, through interaction with others, of the values, attitudes, techniques, and motives for deviant behaviour, on the prediction of academic dishonesty intentions. Additionally, the study tests the effects of Machiavellianism, or dishonest and deceptive behaviours on the relationship between past academic dishonesty acts and academic dishonesty attitudes. Results of the study reveal that differential association with cheating acceptors strengthens the relationship between academic dishonesty attitudes and intentions. Additionally, Machiavellianism at higher levels intensifies the relationships between past academic dishonesty behaviours and contemporary academic dishonesty attitudes.
_eprint: https://doi.org/10.1080/0309877X.2024.2375307
Keywords: Past cheating behaviour; academic dishonesty; cheating; dept.mrk; differential association; machiavellianism; peer-reviewed; social learning